2008
DOI: 10.4085/1062-6050-43.6.600
|View full text |Cite
|
Sign up to set email alerts
|

Occlusive Dressings and the Healing of Standardized Abrasions

Abstract: Context: Acute skin trauma during sport participation, resulting in partial-thickness abrasions, is common. The limited investigations focusing on the acute wound environment and dressing techniques and the subsequent lack of evidence-based standards complicate clinical wound care decisions.Objective: To examine the effects of occlusive dressings on healing of standardized, partial-thickness abrasions.Design: Controlled, counterbalanced, repeated-measures design.Setting: University laboratory.Patients or Other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Wounds heal better with less infection if they are covered with an antibiotic ointment or cream and a clean occlusive dressing (Class IIa, LOE A). [83][84][85] Apply antibiotic ointment or cream only if the wound is an abrasion or a superficial injury and only if the victim has no known allergies to the antibiotic.…”
Section: Wounds and Abrasionsmentioning
confidence: 99%
“…Wounds heal better with less infection if they are covered with an antibiotic ointment or cream and a clean occlusive dressing (Class IIa, LOE A). [83][84][85] Apply antibiotic ointment or cream only if the wound is an abrasion or a superficial injury and only if the victim has no known allergies to the antibiotic.…”
Section: Wounds and Abrasionsmentioning
confidence: 99%
“…Evidence from 2 small, nonrandomized LOE 2 trials in volunteers 208,209 and supportive evidence from 1 LOE 2 human study of other wound types 210 and 3 LOE 5 well-designed animal studies [211][212][213] demonstrated significantly shorter healing time of abrasions treated with any occlusive dressing or topical antibiotic versus no dressing or topical antibiotic.…”
Section: Consensus On Sciencementioning
confidence: 96%
“…HydroTac provides a continuum of hydration that aids wound healing.  Faster wound healing (Winter, 1962;Dyson et al, 1988;Beam et al, 2008)  Promote epithelialisation rate (Winter, 1962;Eaglstein, 2001;Ågren et al, 2001;Varghese et al, 1986;Rubio, 1991;Madden et al, 1989;Wigger-Alberti et al, 2009)  Promote dermal/wound bed healing responses, e.g., cell proliferation, ECM synthesis (Svensjö et al, 2000;Dyson et al, 1992;Mosti, 2013;Korting et al, 2010;Chen et al, 1992;Leung et al, 2010;Field & Kerstein, 1994;Dowsett & Ayello, 2004;Katz et al, 1991)  ReducI can't es scarring (Atiyeh et al, 2003(Atiyeh et al, ,2004O'Shaughnessy et al, 2009;Mustoe & Gurjala, 2011;Tandara et al, 2007;Hoeksema et al, 2013)  Retention of growth factors at wound site (Svensjö et al, 2000;Hackl et al, 2014;Powers et al, 2013;Chen et al, 1992;Attinger et al, 2006;Vogt et al, 1995)  Lower wound infection rates (Kannon & Garret, 1995;Hutchinson & Lawrence, 1991;Lawrence, 1994)  Reduces pain perception (Wiechula, 2003;Metzger, 2004;Leaper et al, 2012;Coutts et al, 2008;Feldman, 1991;...…”
Section: Resultsmentioning
confidence: 99%